Mapping research trends and knowledge structures of rhythmic gymnastics in early childhood gross motor development: A scopus-based bibliometric analysis (2015–2024) - Lusi Angelia; Imam Muthie; Lucy Oktavani; Sri Gusti Handayani; Tisna Syafnita (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Research on rhythmic gymnastics and its contribution to early childhood gross motor development has grown considerably over the past decade. However, the scientific landscape, research trends, and knowledge structures within this field remain insufficiently explored. Aim: This study aimed to map research trends and knowledge structures related to rhythmic gymnastics in early childhood gross motor development through a bibliometric analysis of Scopus-indexed publications. Methods: A systematic literature review with a bibliometric approach was conducted using the Scopus database. A total of 49 eligible articles published between 2015 and 2024 were analyzed. Bibliometric mapping and visualization were performed using VOSviewer, while descriptive analyses were conducted using Microsoft Excel. Results: The findings revealed an increasing publication trend, reaching its highest peak in 2022. Keyword analysis identified strong associations between rhythmic gymnastics and motor skills, motor performance, muscle strength, training, and physical education. Tartu Ülikool emerged as the most productive institutional contributor, while Italy and Spain were the leading countries in publication output. Subject-area analysis showed that medicine and health professions accounted for more than two-thirds of the publications, highlighting the predominance of health-oriented perspectives in this field. Conclusion: The findings demonstrate the growing scientific interest in rhythmic gymnastics as a promising intervention for enhancing early childhood gross motor development. This study provides a comprehensive reference for researchers, educators, and practitioners in developing evidence-based and developmentally appropriate movement programs.